1997
DOI: 10.1007/s11606-006-5002-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival Estimates for Patients with Abnormal Swallowing Studies

Abstract: OBJECTIVE: To better understand the life expectancy of patients who have an abnormal videofluoroscopic swallowing study.DESIGN: Retrospective cohort study. The common starting point was the time of the severely abnormal swallowing study. Hospital charts were reviewed for clinical variables of potential prognostic significance by reviewers blinded to the outcome of interest, survival time.SETTING: A university-affiliated, community teaching hospital. PATIENTS:One hundred forty-nine hospitalized patients who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
2
25
0
3
Order By: Relevance
“…Overall, 119 patients in the dementia group and 129 patients in the nondementia group had dysphagia. We know that the literature supports a 50% death rate at 6 months in patients with end-stage dementia and dysphagia (17). Higaki's study had the diagnosis of dementia confirmed by the criteria of the Diagnostic and Statistical Manual of Mental Disorders (18).…”
Section: Recently Garrow Et Al Performed a Medline Search Viamentioning
confidence: 99%
“…Overall, 119 patients in the dementia group and 129 patients in the nondementia group had dysphagia. We know that the literature supports a 50% death rate at 6 months in patients with end-stage dementia and dysphagia (17). Higaki's study had the diagnosis of dementia confirmed by the criteria of the Diagnostic and Statistical Manual of Mental Disorders (18).…”
Section: Recently Garrow Et Al Performed a Medline Search Viamentioning
confidence: 99%
“…One group instituted a policy requiring PEG placement to wait until 30 days after hospital discharge, and 30-day mortality dropped from 51 percent to 15 percent (Abuksis et al 2004). Cowen, Simpson, and Vettese (1997) developed a model to predict survival based on several risk factors, including age, comorbidity, and baseline serum albumin. Predicted survival at 100 days varied from about 90 percent in the most favorable group to near 0 percent in the least favorable group.…”
Section: What Factors Predict Benefit In Tube Feeding?mentioning
confidence: 99%
“…Advanced age, low serum albumin, accompanying comorbidity, dementia or pulmonary aspiration (as the indication for PEG referral) and a documented abnormal swallow study, have all been recognised as independent risk factors which predict a poor outcome (Table 1). 5,6,10,13,[30][31][32][33] An effective strategy for PEG insertion?…”
Section: Indicators Of Poor Prognosis Following Peg Insertionmentioning
confidence: 99%